Emergence of Shiite Salafism in Iran and their Ideological Confrontation with Shiites - Seyed Mostafa Hosseini (پژوهش‌نامه کلام تطبیقی شیعه, 2019)
When the question of reform in religion came into play, some currents of thought aimed at reforming religious affairs. One of these currents that took place in the Muslim world was the Salafist movement. In Iran, some influenced by Salafists emerged who had similar beliefs. Other factors contributed to the formation of this trend in Iran, including the weakness and decline of Muslims and the progress of the West in the material sciences and the cooperation of the rulers of the time and Western factors with them. Proponents of this movement initially chanted only the slogan of returning to the Qur'an and the beginning of Islam, but after a while, some Muslim beliefs, especially Shiites, saw differences between Muslims and the spread of superstitions, and they began to deny them. Like what they say in Imamate, infallibility, and science of the Imams, intercession, Visiting graves, and pilgrimage. Other important beliefs of the group include calling for unity and fighting against the clergy and the abandonment of many traditions. The present article investigates this process including its formation, beliefs, and introducing some of their personalities (Khorghani, Sanglji, Borghi, Ghalamdaran, and Tabataba'i).